Administrative and Legal Status of the Assessment and Disciplinary Board of Prosecutors - V. Yu. Tsebinoga (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article has studied the administrative and legal status of the Assessment and Disciplinary Board of prosecutors. The normative and legal base regulating the administrative and legal status of the Assessment and Disciplinary Board of prosecutors has been determined. The elements of the administrative and legal status of the Assessment and Disciplinary Board of prosecutors have been established. The problems of implementing the administrative and legal status of Assessment and Disciplinary Board of prosecutors have been noted.